Public Policy and Research in Africa - Aiyede, E. Remi; Muganda, Beatrice (Springer Nature, 2023)
This open access book responds to the need for a specifically African focus on public policy. It outlines the fundamental principles of public policy research, and engages with major issues in the study of public policy from an African perspective, covering essential topics such as the location and centrality of social sciences in relation to public policy, leadership, methodology, institutions, governance, and gender. This book is essential for understanding the various aspects and dimensions of policy making in Africa that underscore quality research and are at the core of excellence in teaching and learning.